2010
DOI: 10.1080/15567030802612168
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Biodiesel Production from Cottonseed Oil by Transesterification Using NaOH and Methanol

Abstract: In this study, the transesterification of cottonseed oil with methanol was carried out using NaOH. The parameters, such as molar methanol:oil ratio, NaOH %, and temperature effecting the yield and biodiesel quality, were investigated to optimize biodiesel production from cottonseed oil. Below 50 ı C, transesterification of cottonseed oil was not completed at any molar methanol:oil ratios and catalyst percentages in 1 h. In 3:1 methanol:oil ratio, full conversion was not observed. Optimum conversion was obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The PW12 was shown to be an efficient catalyst for the production of environmentally compatible biodiesel fuel in high yields. Cottonseed oil is available as the byproduct of cotton with low price because it is not preferred much as edible oil (Shu et al, 2009;Fan et al, 2010;Hoda, 2010). The starch-derived catalyst was further tested for the conversion of waste cottonseed oils containing high free fatty acids (55.2 wt.% FFAs), in the presence of methanol, to FAME by simultaneous esterification and transesterification.…”
Section: Biodiesel Production From Waste Cottonseed Oil With Starchdementioning
confidence: 99%
“…The PW12 was shown to be an efficient catalyst for the production of environmentally compatible biodiesel fuel in high yields. Cottonseed oil is available as the byproduct of cotton with low price because it is not preferred much as edible oil (Shu et al, 2009;Fan et al, 2010;Hoda, 2010). The starch-derived catalyst was further tested for the conversion of waste cottonseed oils containing high free fatty acids (55.2 wt.% FFAs), in the presence of methanol, to FAME by simultaneous esterification and transesterification.…”
Section: Biodiesel Production From Waste Cottonseed Oil With Starchdementioning
confidence: 99%
“…[18,19] Epoxidation is another way of using this oil since the global production was 5 million tons in 2011 [20] and its potential in the composites' industry is really promising.…”
Section: -Introductionmentioning
confidence: 99%
“…The higher oxygen content of COME shows negative effects on the formation of smoke and particulate matter (PM) emissions, while the higher density and viscosity show opposite effects. As a result, for COME-diesel blends, the smoke and PM emissions are just slightly decreased when small amount of COME is added under the low-and middle-engine loads Bayindir 2010a, 2010b;Bayindir 2010;Hoda 2010).…”
Section: Introductionmentioning
confidence: 92%
“…Cottonseed oil produced ETHYLENE GLYCOL MONOMETHYL ETHER COTTONSEED OIL MONOESTER 377 from cotton plants is one of the main vegetable oils supplied for food and other chemicals in China and other areas in the world. The formation, engine performance, as well as emission characteristics of biodiesels derived from cottonseed oil (mainly the cottonseed oil methyl ester (COME)) were widely investigated in most countries such as Brazil (Simoni, Mario, and Tatiana 2007), China (Yao, Ji, and Sun 2010), India (Syed, Raja, and Gopal 2009), Turkey Bayindir 2010a, 2010b;Bayindir 2010;Hoda 2010), the USA (Umer, Farooq, and Gerhard 2009), and so on. Previous studies indicated that, compared to diesel fuel, COME has lower UHC, CO, and SO x emissions, but higher NO x emission.…”
Section: Introductionmentioning
confidence: 99%